Athletic Rosters of Tufts University for the year 1956 - Kenny, Maura; Sauer, Anne; Crowley, Zachary E. (Tufts Archival Research Center, 2008)
The Athletics Rosters of Tufts University is the result of a project to collect and record the participants in organized athletics at Tufts University. The names contained in these rosters were compiled from the records of the Department of Physical Education/Athletics and particularly the Athletic Association Meeting Minutes and team files, as well as publications such as student newspapers, the Tuftonian, the Brown and Blue, and the Jumbo Book.